2021
DOI: 10.3390/socsci10060236
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence, Predictors, and In-Group Differences of Forced Sex and Physical Dating Violence among Trans/Gender Diverse Youth

Abstract: Forced sex and dating violence are too common among young people and rates are higher for young transgender and gender diverse (TGD) individuals. However, the TGD youth population has differential experiences across gender, race, age, sexual orientation, and other identity factors. This study, using data from the 2015 Healthy Kids Colorado Survey, explores these differential within-group experiences of forced sex and dating violence. Findings indicate that sexual minorities who are also TGD are 2.45–3.73 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Even when folks do not live traditional or normative manifestations of gender, they understand the norms and expectations of gender and how masculinity and femininity should be performed (Lindley et al, 2022). More importantly, they are also aware of the risks associated with living outside the norms, and they are aptly able to engage in behaviors in a way that calculates the risks associated with their gender performance, and understand how their behavior will or will not be classified (Kattari et al, 2021;Lindley et al, 2022;West & Zimmerman, 1987;Zamantakis, 2020).…”
Section: Doing Gender and Receiving Gendermentioning
confidence: 99%
“…Even when folks do not live traditional or normative manifestations of gender, they understand the norms and expectations of gender and how masculinity and femininity should be performed (Lindley et al, 2022). More importantly, they are also aware of the risks associated with living outside the norms, and they are aptly able to engage in behaviors in a way that calculates the risks associated with their gender performance, and understand how their behavior will or will not be classified (Kattari et al, 2021;Lindley et al, 2022;West & Zimmerman, 1987;Zamantakis, 2020).…”
Section: Doing Gender and Receiving Gendermentioning
confidence: 99%
“…The survey revealed that approximately 22% of married women in Rwanda have encountered domestic violence, with 14% reporting instances of sexual violence by their partners. Compared to regional statistics, these numbers underscore the impact of cultural, historical, and socioeconomic factors in sub-Saharan Africa (20)(21)(22)(23).…”
mentioning
confidence: 95%